Three-dimensional shape measurement using fiber optic low-coherence speckle interferometry - Balboa, Itziar; Tatam, Ralph P. (SPIE - International Society for Optics and Photonics, 1998)
A low coherence speckle interferometer implemented using single mode optical fibre and a multimode laser diode as a pseudo-low coherence source is described. The design of the interferometer is presented and demonstrated on simple test objects. Signal processing techniques to improve the performance ofthe system are discussed.
SPIE's International Symposium on Optical Science, Engineering, and Instrumentation, 1998, San Diego, CA, United States
Keywords: peckle interferometry; ow coherence sources; surface profile measurement